Fabrication of self‐organized precisely tunable plasmonic SERS substrates via glancing angle deposition. Issue 9 (16th May 2017) - Rezvani, Ehsan; Ualibek, Oral; Bulfin, Brendan; Sugurbekova, Gulnar; Duesberg, Georg Stefan; Shvets, Igor
Abstract : Plasmonic nanostructures offer great enhancement of the Raman signal due to the strong confinement of the electromagnetic field. Thus, they are considered as suitable candidates for surface enhanced Raman spectroscopy (SERS). In this work, we present an alternative fabrication route, called the glancing angle deposition (GLAD), for tunable fabrication of plasmonic self‐organized Ag nanoparticle arrays aimed at SERS. Using the GLAD technique, the inter‐particle distance within the arrays can be made as small as 1 nm. Moreover, the plasmonic resonance can be precisely tuned over the whole visible range. The GLAD method can be up‐scaled; and when a transparent substrate is used, it enables various measurement geometries. The enhancement factor for the employed probe molecule in this study, rhodamine 6G, is estimated to be in the order of ∼10 8 . It is noted that the nature of the GLAD‐made substrates leads to the polarization dependence of the signal enhancement. The polarization studies show a stronger enhancement along the nanoparticles chain.